Direct measurement of the free cyclotron frequency of a single particle in a penning trap - Ulmer, Stefan; Blaum, Klaus; Kracke, H.; Mooser, A.; Quint, Wolfgang; Rodegheri, C. C.; Walz, J. (Physical review letters, 2011)
A measurement scheme for the direct determination of the free cyclotron frequency νc of a single particle stored in a Penning trap is described. The method is based on the dressed states of mode coupling. In this novel measurement scheme both radial modes of the single trapped particle are simultaneously coupled to the axial oscillation mode.